(3GdbjGOI GdEOGQjI aj GdESdGe (B/s - (3CHh GdaVd, YHO GdTGaj eMeOs ((3gjQfOf(B: s (3GdeYgO GdYGdej ddacQ GdGSdGej(B, s, 1996)
(3gPG GdcJGH jUOQ aj SdSdI OQGSGJ GdEbJUGO GdESdGej GdJj jUOQgG GdeYgO GdYGdej ddacQ GdESdGej hjJfGhd gPG GdcJGH JfXje YdGbJ GdeDSSGJ ShGA cGfJ eY ZjQgG ef GdCaQGO hGdeDSSGJ GdCNQi , Ch aj LGfH GSJNOGeJgG ddCehGd GdeJGMI dgG ,Ch aj LGfH GdNOeGJ GdCNQi YfO GdJehjdjI GdJj Jbhe HgG hbO NUU gPG GdcJGH aj aUhdg GdeJYOOI ehVhY GdbjGOI GdEOGQjI aj GdESdGe ef NdGd ebheGJ hYfGUQ GdbjGOI aj GdacQ GdEOGQj GdeYGUQ hJMdjd hefGbTI efGgL GdHMK hYedjGJ GdbjGS GdeSJNOeI aj OQGSI GdXGgQIs
(3GdeQGLY U(B.299s
Keywords: (3GdESdGe hGdGbJUGOs; (3JfXje hGOGQIs